Parameter Estimation Technique Of Nonlinear Prosthetic Hand System - Rozaimi, Ghazali (Engg Journals Publications, 2016)
This paper illustrated the parameter estimation technique of motorized prosthetic hand system.Prosthetic hands have become importance device to help amputee to gain a normal functional hand.By integrating various types of actuators such as DC motor,hydraulic and pneumatic as well as mechanical part,a highly useful and functional prosthetic device can be produced. One of the first steps to develop a prosthetic device is to design a control system. Mathematical modeling is derived to ease the control design process later on.This paper explained the parameter estimation technique of a nonlinear dynamic modeling of the system using Lagrangian equation.The model of the system is derived by considering the energies of the finger when it is actuated by the DC motor.The parameter estimation technique is implemented using Simulink Design Optimization toolbox in MATLAB.All the parameters are optimized until it achieves a satisfactory output response.The results show that the output response of the system with parameter estimation value produces a better response compare to the default value